2013
DOI: 10.1007/s11010-013-1919-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorogenic acid, caffeine, and coffee on behavioral and biochemical parameters of diabetic rats

Abstract: Diabetes mellitus (DM) is associated with brain alterations that may contribute to cognitive dysfunctions. Chlorogenic acid (CGA) and caffeine (CA), abundant in coffee (CF), are natural compounds that have showed important actions in the brain. The present study aimed to evaluate the effect of CGA, CA, and CF on acetylcholinesterase (AChE), Na(+), K(+)-ATPase, aminolevulinate dehydratase (δ-ALA-D) activities and TBARS levels from cerebral cortex, as well as memory and anxiety in streptozotocin-induced diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…Recent researches on chlorogenic acid suggest that it inhibits DNA damage and lipid peroxidation by increasing the resistance of low-density lipoprotein (Wan et al 2013) and prevents carcinogenesis by reducing DNA damage (Rakshit et al 2010;Ooi et al 2011). It has also been reported to have analgesic (Hara et al 2014), antiinflammatory (Hwang et al 2014), antidiabetic (Stefanello et al 2014), and antibacterial effects (Ozçelik et al 2011). Vanillic acid (4-hydroxy-3-methoxybenzoic acid) is a benzoic acid derivative found in plant and fruits that is being used as a preservative and antiseptic agent in cosmetic, food, and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches on chlorogenic acid suggest that it inhibits DNA damage and lipid peroxidation by increasing the resistance of low-density lipoprotein (Wan et al 2013) and prevents carcinogenesis by reducing DNA damage (Rakshit et al 2010;Ooi et al 2011). It has also been reported to have analgesic (Hara et al 2014), antiinflammatory (Hwang et al 2014), antidiabetic (Stefanello et al 2014), and antibacterial effects (Ozçelik et al 2011). Vanillic acid (4-hydroxy-3-methoxybenzoic acid) is a benzoic acid derivative found in plant and fruits that is being used as a preservative and antiseptic agent in cosmetic, food, and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Padma et al (2012) demonstrated reduction in lipid levels peroxidation in all structures tested significantly (Figure 4a, b, c and d). Therefore, chlorogenic acid and quercetin, both identified in the infusion of M. nigra, were capable to decrease MDA levels in serum, erythrocytes, cerebral cortex, hippocampus and liver (Jung et al 2009, Meng et al 2013, Stefanello et al 2014, Xia et al 2015, Imessaouedene et al 2016.…”
Section: Effect Ofmentioning
confidence: 99%
“…One possible strategy to correct the changes in synaptic efficiencies caused by DM can be through of analysis of the presynaptic neuromodulation systems, as purinergic system [11,12]. Adenine nucleotides represent an important class of extracellular molecules involved in modulation of signaling pathways that are essential to the normal functioning of the central nervous system (CNS) [13].…”
Section: Introductionmentioning
confidence: 99%